2018
DOI: 10.1128/mspheredirect.00597-18
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Monolaurate (GML) and a Nonaqueous Five-Percent GML Gel Kill Bacillus and Clostridium Spores

Abstract: Bacillus and Clostridium spores are known to be highly resistant to killing, persisting on environmental and human body surfaces for long periods of time. In favorable environments, these spores may germinate and cause human diseases. It is thus important to identify agents that can be used on both environmental and human skin and mucosal surfaces and that are effective in killing spores. We previously showed that the fatty acid monoester glycerol monolaurate (GML) kills stationary-phase cultures of Bacillus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 31 publications
1
20
4
Order By: Relevance
“…As a consequence, we chose to investigate the effects of a GMLg on highly purified spores of B. cereus , B. subtilis, B. megaterium and C. difficile , in particular with the hope of determining how spores are killed by this agent. However, we observed no killing of the purified spores of these species by GMLg using conditions identical to those used in the recent work reporting large amounts of spore killing by a GMLg (Schlievert et al 2018). In collaborative studies with the Schlievert laboratory, only up to 1·5 logs of killing of a crude preparation of B. subtilis was observed in 24 h. The major reason for the apparent killing of spores in the prior manuscript was carryover of GMLg, with prevention of spore germination or spore killing upon germination.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…As a consequence, we chose to investigate the effects of a GMLg on highly purified spores of B. cereus , B. subtilis, B. megaterium and C. difficile , in particular with the hope of determining how spores are killed by this agent. However, we observed no killing of the purified spores of these species by GMLg using conditions identical to those used in the recent work reporting large amounts of spore killing by a GMLg (Schlievert et al 2018). In collaborative studies with the Schlievert laboratory, only up to 1·5 logs of killing of a crude preparation of B. subtilis was observed in 24 h. The major reason for the apparent killing of spores in the prior manuscript was carryover of GMLg, with prevention of spore germination or spore killing upon germination.…”
Section: Introductionsupporting
confidence: 63%
“…As a consequence, there is a continuous interest in the development of new treatments to facilitate spore killing, which can be difficult because of spores’ extreme resistance to all kinds of chemical agents (Setlow 2006; Setlow and Johnson 2019). One type of agent that has garnered some interest for its effects on spores is monoglyceryl esters of medium‐chain fatty acids, with GML the one that has been most investigated (Chaiba et al 1996a, 1996b; Mansour et al 1999; Shearer et al 2000; Lopes et al 2016; Schlievert et al 2018). In some of these reports (Chaiba et al 1996a, 1996b; Mansour et al 1999), GML was reported to inhibit the germination of spores of several Bacillales species, although the precise mechanism of this germination inhibition was not determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that MCFAs and monoglycerides often exhibit greater antibacterial potency than commonly studied organic acids (e.g., lactic and citric acids) [39]. It has also been determined that compounds within this class, such as GML, can exhibit nearly complete killing of vegetative cells and spores of aerobic B. anthracis, B. subtilis, and B. cereus and anaerobic Clostridium perfringens and Clostridium (Clostridioides) difficile [40]. Another study has reported that GML and lauric acid also inhibit Listeria monocytogenes, which is a foodborne pathogen that can contaminate swine farms [27].…”
Section: Spectrum Of Antimicrobial Activitymentioning
confidence: 99%
“…92 Lastly, a recent report has shown that a nonaqueous gel of glycerol monolaureate can kill C. difficile spores, suggesting that this antimicrobial could be used as a method for decontaminating environmental surfaces as well as skin. 93…”
Section: Difficile Spores Resist Commonly Used Disinfectants But Amentioning
confidence: 99%